Analisis Kinerja Mikrotik Omnitik Sebagai Pendeteksi Interferensi Frekuensi Di Balai Monitoring Spektrum Frekuensi Radio Lampung - Priyatna, Aziz; Triloka, Joko (INTEGER: Journal of Information Technology, 2024)
The Meteorology, Climatology, and Geophysics Agency (BMKG) is a government institution responsible for providing meteorological, climatological, and geophysical information and services in Indonesia. Currently, the process of monitoring and checking frequency interference by the Class II Radio Frequency Spectrum Monitoring Center in Lampung is carried out by visiting predetermined location points based on coordinates. Then, the inspection team checks using radar, and the results of the inspection are reported to the Radio Frequency Spectrum Monitoring Center. This checking process takes a long time because the inspection of frequency disturbances is done gradually from point to point. There is a need for innovation to expedite the checking and handling of frequency interference so that these issues can be detected and resolved more quickly. One of the solutions is the development of a sistem utilizing Mikrotik Omnitik sensors to detect frequency interference at the Lampung radio frequency spectrum monitoring center. The sistem created can scan and detect frequencies experiencing interference operating at 5GHz with a data transmission speed of 1.05 seconds.